Structure and Biophysics - New Technologies for Current Challenges in Biology and Beyond - Puglisi, Joseph D. (Nato Security through Science Series B:, Physics and Biophysics,, 2007)
This volume is a collection of articles from the Proceedings of the International School of Structural Biology and Magnetic Resonance 7th Course: Structure, Structure and Biophysics - New Technologies for Current Challenges in Biology and Beyond. This NATO Advance Study Institute (ASI) was held in Erice (Italy) at the Ettore Majorana Foundation and Centre for Scientific Culture on 22 June through 3 July 2005. The ASI brought together a diverse group of experts in the fields of structural biology, biophysics, and physics. Prominent lecturers, from seven different countries, and students from around the world participated in the NATO ASI organized by Professors Joseph Puglisi (Stanford University, California, USA) and Alexander Arseniev (Moscow, RU). Advances in nuclear magnetic resonance (NMR) spectroscopy and X-ray crystallography have allowed the thr- dimensional structures of many biological macromolecules and their complexes, including the ribosome and RNA polymerase to be solved. Fundamental principles of NMR spectroscopy and dynamics, X-ray crystallography, computation, and experimental dynamics were taught in the context of important biological applications. The ASI addressed the treatment and detection of bioterrorism agents, and focused on critical partner country priorities in biotechnology, materials, and drug discovery. The range of topics here represents the diversity of critical problems between structural biology, biochemistry, and biophysics, in which lies the fertile ground of drug development, biotechnology, and new materials. The individual articles represent the state of the art in each area and provide a guide to the original literature in this rapidly developing field.